Climate Change, Energy, Sustainability and Pavements - Gopalakrishnan, Kasthurirangan; Steyn, Wynand JvdM; Harvey, John (Green Energy and Technology,, 2014)
Climate change, energy production and consumption, and the need to improve the sustainability of all aspects of human activity are key inter-related issues for which solutions must be found and implemented quickly and efficiently.  To be successfully implemented, solutions must recognize the rapidly changing socio-techno-political environment and multi-dimensional constraints presented by today's interconnected world.  As part of this global effort, considerations of climate change impacts, energy demands, and incorporation of sustainability concepts have increasing importance in the design, construction, and maintenance of highway and airport pavement systems.  To prepare the human capacity to develop and implement these solutions, many educators, policy-makers and practitioners have stressed the paramount importance of formally incorporating sustainability concepts in the civil engineering curriculum to educate and train future civil engineers well-equipped to address our current and future sustainability challenges. This book will prove a valuable resource in the hands of researchers, educators and future engineering leaders, most of whom will be working in multidisciplinary environments to address a host of next-generation sustainable transportation infrastructure challenges. "This book proposes a broad detailed overview of the actual scientific knowledge about pavements linked to climate change, energy and sustainability at the international level in an original multidimensional/multi-effects way. By the end, the reader will be aware of the whole global issues to care about for various pavement technical features around the world, among which the implications of modelling including data collection, challenging resources saving and infrastructures services optimisation. This is a complete and varied work, rare in the domain." Dr. Agnes Jullien Research Director Director of Environmental, Development, Safety and Eco-Design Laboratory (EASE) Department of Development, Mobility and Environment Ifsttar Centre de Nantes Cedex- France.